Pengembangan Dan Perubahan Organisasi Seiring Dengan Reinventing Dalam Sistem Organisasi Pendidikan - Riska Suci Febriani; Muhammad Syaifudin; Tuti Andriani (LPPM Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The aim of organizational development, especially educational organizations, is the formation of educational organizations within the provincial and district/city governments, so that educational units at all types and levels are open and generate trust for educators and the community. The organization is open and generates trust for educators and their community. Organizational development interventions tend to emphasize the application of collaborative or interpersonal and group strategies in coordinative or vertical inter-organizational action, in keeping with the spirit of reinvention. In the restructuring of education organizations or reinvented education to improve the activities and programs of the Provincial, District and City Education Offices in carrying out routine activities it must be changed, no longer using a bureaucratic approach with a participatory approach. The paradigm of the education apparatus must be changed, so that it is in accordance with the spirit of implementing school-based management in schools. By giving a big role to schools in the spirit of change, schools have high creativity to compete in improving the quality and quality of education in these schools